2022
DOI: 10.1007/s00044-022-02921-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the α-glucosidase and α-amylase inhibitory potential of Paliurus spina-christi Mill. and its terpenic compounds

Abstract: Type II diabetes mellitus is a common disease in the world and characterized by hyperglycemia. Prevention of diabetes by reducing hyperglycemia depends on the inhibition of α-amylase and α-glucosidase enzymes. In this study, antidiabetic pro les of Paliurus spina-christi Mill. phytochemicals and extracts were investigated. The plant is used in folk medicine in Turkey as antidiabetic. α-Amylase and α-glucosidase inhibitory effect studies were conducted to prove this effect. The n-hexane extract (IC 50 = 445.7 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Previous studies on lupeol and betulin and betulinic acid mixture reported good α-amylase and α-glucosidase inhibitory activities, and another work on amentoflavone showed its potent inhibitory activity against α-glucosidase. ( Rathinavel et al, 2021 , Yuca et al, 2022 , Li et al, 2023 ). Molecular docking analysis was performed to explore the binding modes of our isolated phytochemicals against α-glucosidase.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on lupeol and betulin and betulinic acid mixture reported good α-amylase and α-glucosidase inhibitory activities, and another work on amentoflavone showed its potent inhibitory activity against α-glucosidase. ( Rathinavel et al, 2021 , Yuca et al, 2022 , Li et al, 2023 ). Molecular docking analysis was performed to explore the binding modes of our isolated phytochemicals against α-glucosidase.…”
Section: Discussionmentioning
confidence: 99%
“…We used the method of Yuca et al [ 26 ], with slight modifications. The α-amylase solution (1 U/mL) was mixed into samples at varying concentrations and preheated in 37 °C water bath for 5 min, followed by addition of 1% preheated starch solution.…”
Section: Methodsmentioning
confidence: 99%
“…Among the phenolic compounds isolated from C. humilis methanol extract in this study, myricetin, avicularin, pruning, quercitrin, guajavarin and isoquercitrin were accountable for their α-glucosidase activity. The Paliurus spina-christi mill fruit is used as an antidiabetic traditional medicine in Turkey, and a recent study showed that n -hexane fractions derived from the methanolic fruit extract have remarkably higher α-glucosidase inhibitory effects than acarbose with IC 50 of 445.7 ± 8.5 and 4212.6 ± 130.0 µg/mL, respectively [ 85 ]. The phytochemical analysis of the fruit extract identified three terpenic compounds (betulin, betulinic acid and lupeol) with a higher α-glucosidase inhibitory activity than acarbose.…”
Section: Plant Extracts As α-Glucosidase Inhibitor Sourcesmentioning
confidence: 99%
“…Recently, Yuca et al evaluated the antidiabetic properties of the triterpenes isolated from Paliurus spina-christi mill fruit. Interestingly, the mixture of betulin ( Figure 5 c) and betulinic acid ( Figure 5 d) mixture (IC50 = 248 ± 12 µM) inhibited α-glucosidase 26 times better than acarbose (IC50 = 6561 ± 207 µM) [ 85 ]. In light of these findings, it may be intriguing to study the synergistic and antagonistic effects of various terpenoid compounds on α-glucosidase inhibition.…”
Section: Plant-derived Bioactive Compounds As Potential α-Glucosidase...mentioning
confidence: 99%